Características fenológicas e produtivas da goiabeira "Paluma" podada em diferentes épocas e intensidade no município de Mossoró - RN - Farias, Wagner César de (2015)
The pruning allows fruit picking in times desired by the producer and is economically viable, because it can allow the harvest precisely in periods of reduced supply in the market. Its implementation can also be programmed in order to better distribute the cultivation of the orchard and to bringing more flexibility in marketing. Thus the knowledge of phenological characteristics in specific growing conditions allows more precise programming of cultural and phytosanitary treatments and therefore more efficient management practices, given thus the global trend of adoption of good agricultural practices. The experiment was conducted in the didactic orchard of the Federal Rural University of the Semi -Arid (UFERSA), from April 2013 to December 2014, in the municipality of Mossoro-RN. It was arranged in a randomized block design, with treatments arranged in a split-plot, which were composed by pruning times, conducted in April (2013), November (2013) and July (2014); and subplots by pruning intensities (heavy, medium and light); with four replications, where the experimental unit consisted of two plants that was pruned and had 8 branches marked with colored ribbons. From the day of pruning to harvest, were evaluated in marked branches, the following botanical characteristics: number of sprouts issued by branch pruned to 15 days (NBE); number of branches established by branch pruned to 50 days (NRE); number of branches (NRP); vegetative number (VRN) and the total number of fruits (NFT). The objective of this work was the phenological and productive characterization of guava "Paluma" subjected to different times and pruning intensities in region Mossoro-RN. It was observed that all traits showed significant effects. The best pruning was the long, which obtained the highest number of fruits in every age. The best time to carry out the pruning were the months of November and July. The duration of guava cycle "Paluma" harvest pruning of fruit varies with the time of day of winter pruning, lasting from 132 in July to 150 days in April